Odnos zaposlenih v Zdravstvenem domu Center do uporabnikov metadonske ambulante - Debevec-Švigelj, Metka (Obzornik zdravstvene nege, 1999)
The article discusses the attitude of the staff of Health Center Ljubljana-Center (HC) towards the clients of methadone clinic (MC) in the Center. The introductory part presents the attitude towards illegal drug dependence, methods of the fight against drug use and methods of treatment of drug dependence, with the stress on maintenance methadone program as a part of the treatment process, illustrated by the concrete example of methadon clinic in the frames of HC. In the empirical part of the present work, the knowledge about the operation and doctrine of the methadone clinic among the staff of the HC Ljubljana-Center, their concept of dependence and goals of methadone maintenance in a health center, their attitude towards an "average" drug addict and their attitude towards the staff of the methadone clinic was investigated. The results reveal relation between attitudes and gender, age, education level the distance between workpost and methadone clinic, place of living and the knowledge of the operation of methadon clinic. The discussion part states that the hypotesis of intolerance of the staff in HC Ljubljana-Center against clients of methadone was confirmed. The staff of the HC do not generally have a negative attitude towards an average drug addict; still, they would rather avoid them. In spite of the fact that they acknowledge the necessity of a methadone clinic, they would rather not have in their health center.
Keywords: (RS)-methadones; droge; metadon; odnos zdravnik-bolnik; odvisnosti; zasvojenost; zdravstveni delavci